Bio-inspired hierarchical micro- and nano-wrinkles obtained via mechanically directed self-assembly on shape-memory polymers. Issue 24 (15th May 2017) - Schauer, Senta; Worgull, Matthias; Hölscher, Hendrik
Abstract : Inspired by buckling in nature, we generated hierarchical surface wrinkles in a full-polymer system based on a shape-memory polymer substrate. Abstract : Inspired by complex multi-functional leaf and petal surfaces, we introduce a mechanically directed self-assembly process to create linearly oriented micro- and nanosized surface wrinkles in an all-polymer bi-layer system based on a shape-memory polymer substrate. By systematically investigating the influence of coating thickness and substrate programming strain on wrinkle period and height, we reveal how to control the structure size from a few hundred nanometers up to several microns. As a parameter unique to shape memory polymers, we demonstrate that the temperature during the recovery process can also be utilized to tailor the structure dimensions. Furthermore, we advance the method with a second structuring step to mimic the hierarchically structured petal surfaces of tulips and daisies. The presented structuring method provides a large-scale, mold-free, and very cost-effective way for the full-polymer fabrication of micro and sub-microstructures with adjustable structure size and intrinsic irregularity.